Process of accepting the disease: a self-management of patient with Nasopharyngeal cancer - Che Abdullah, Che Azunie; Saidi, Sanisah; Lee, Siew Pien; Asha'ari, Zamzil Amin (IIUM Press, 2023)
Background: To understand and explore in-depth the self-management experience of patients with nasopharyngeal cancer when accepting the cancer diagnosis as part of their cancer trajectory. Methods: An exploratory qualitative case study design was conducted based on the study objective. One-on-one in-depth semi-structured interviews were held among patients diagnosed with nasopharyngeal cancer (N=16) of two primary hospitals in Malaysia by using purposive sampling. Data were transcribed verbatim and analysed using framework analysis approach (data management, descriptive account, explanatory account). Results: This article presents patients’ experiences during diagnosis and how they managed this situation. A theme called the Process of accepting the disease emerged to portray this experience with a subtheme - emotional changes and management when they receive their nasopharyngeal cancer diagnosis. Feelings and situations were described by emotional discouragement and embracing fate, which had been self-managed by avoidance and trying to comprehend. Conclusion: Patients experienced grief like other types of cancer patients, although nasopharyngeal cancer was reported to have a good prognosis with effective treatment provision. They were burdened by the cancer diagnosis and avoided having thought about it while struggling to comprehend their own health. It was evidenced that patients critically need and profound for health information related to various aspects of cancer and treatment during this phase. Therefore, these findings strongly recommend that healthcare professionals to address this need particularly among those who are newly diagnosed with nasopharyngeal cancer to help them accepting their cancer diagnosis.